Niobium Uptake and Release by Bacterial Ferric Ion Binding Protein - Yanbo Shi; Ian Harvey; Dominic Campopiano; Peter J. Sadler (Bioinorganic Chemistry and Applications)
Ferric ion binding proteins (Fbps) transport FeIII across the periplasm and are vital for the virulence of many Gram negative bacteria. Iron(III) is tightly bound in a hinged binding cleft with octahedral coordination geometry involving binding to protein side chains (including tyrosinate residues) together with a synergistic anion such as phosphate. Niobium compounds are of interest for their potential biological activity, which has been little explored. We have studied the binding of cyclopentadienyl and nitrilotriacetato NbV complexes to the Fbp from Neisseria gonorrhoeae by UV-vis spectroscopy, chromatography, ICP-OES, mass spectrometry, and Nb K-edge X-ray absorption spectroscopy. These data suggest that NbV binds strongly to Fbp and that a dinuclear NbV centre can be readily accommodated in the interdomain binding cleft. The possibility of designing niobium-based antibiotics which block iron uptake by pathogenic bacteria is discussed.